ANALSIS PROSFEK DAN STRATEGI PENGEMBANGAN KOMODITI UNGGULAN RUMPUT LAUT DI KABUPATEN WAJO - Nasriah Akil (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
This research is aimed to know prospect and strategy of seaweed commodity development in wajo regency. The research method used in this research is using SWOT analysis method. The results of this study show that business actors having the strongest bargaining position in the seaweed value chain in Wajo are exporter traders, while the weakest are seaweed farmers. The management of value chains between suppliers of seaweed and seaweed products with consumers is the market. In the value chain, collecting traders play a role in supplying fish production facilities, while seaweed farming is done by farmers. The lowest income earners are farmers (Rp 200 s.d. Rp 300 / kg dried seaweed), while the highest income earners are large collectors (Rp 300 s.d. Rp 700 / kg dried seaweed). Convert grass products at farmer level from dried product to processed products (ATC and SRC) for export, Form seaweed clusters initiated from cultivators. The three main priorities of seaweed cultivation development strategy in Wajo Regency are: To streamline the role of Marine and Fisheries Office, and related institutions in the development and development of human resources; Increase in the source of business capital; Procurement of cooperation pattern of market partnership.